Towards sustainable, productive and profitable agriculture: Case of rice and sugarcane - Ashok Gulati; Gayathri Mohan (Indian Council for Research on International Economic Relations (ICRIER), 2018)
Indian agriculture is estimated to be consuming about 78 percent of total fresh water resources available in the country. Yet, more than half of the gross cropped area is still dependent on rains. Extremely skewed allocation of scarce irrigation water amongst crops and inefficient use of the allocated water are major reasons behind this paradox. Water guzzler crops like rice and sugarcane, occupying about one-fourth of the gross cropped area, consume more than 60 per cent of irrigation water available in the country. Hence if sustainable agriculture water-use has to be ensured, economics (productivity and profitability) of at least these two crops needs to be studied thoroughly to see how best higher productivity and profitability can be achieved with lesser amounts of irrigation water. This is what is attempted in this paper. The study shows that regions like Punjab and Haryana, which have high land productivity of rice, fall way below in ranking of irrigation water productivity. Instead, eastern states like Bihar, eastern UP give better results, highlighting the need to shift rice cultivation from north-western states to eastern states. Similar results are obtained for sugarcane in Maharashtra, Tamil Nadu and Karnataka, which are high on land productivity but low on irrigation water productivity, suggesting that sugarcane cultivation needs to shift from tropical to sub-tropical states of Bihar and Uttar Pradesh. In order to encourage such cropping pattern shifts, both in rice and sugarcane, one will have to undertake reforms related to water/energy policies, institutions and technologies related to irrigation water use. Some of our policy suggestions are: 1) Implement price policies that reflect the scarcity and economic value of water and power use in agriculture, while improving the quality and timely availability of these to farmers 2) Strengthen marketing opportunity of sugarcane and procurement policies of rice in the water abundant states of eastern region. At the same time, set the markets right (reduce market risk) for the less water intensive crops that give much higher value per cubic meter of irrigation water applied in water scarce states 3) Direct Benefit transfer of water and power subsidies to farmers 4) If price reforms with DBT of water and power subsidies are not possible, ration irrigation water and power used in agriculture on per hectare basis, and then let the water markets operate amongst farmers 5) Adopt irrigation technologies and practices that encourage water savings, such as micro irrigation system in sugarcane and rice.
Keywords: O13; Q01; Q15; Q18; Q25; 330; Water Guzzler Crops; Irrigation Water Productivity; Sustainability; Profitability; Cropping Pattern; Water Stress